Multisystem pediatric inflammatory syndrome associated with COVID-2019 in the Zaporizhzhia region - O. V. Usachova; D. V. Aleksiuk (Zaporozhye State Medical University, 2023)
The aim is to familiarize with the clinical signs of the multisystem inflammatory syndrome associated with COVID-19, based on the analysis of its course in children of the Zaporizhzhia region of Ukraine. Materials and methods. A retrospective analysis of the medical histories of 16 children, aged from 1 to 16 years, who had a history of COVID-19 and/or who were in contact with patients with this disease and had a confirmed disease accompanied by fever, disorders of other organs and systems, was conducted. The methods of non-parametric statistics - descriptive statistics and statistical inference - were used for statistical processing of the results. All calculations were carried out using Microsoft Excel. Results. Symptoms found in the examined children met the following WHO diagnostic criteria for multisystem pediatric inflammatory syndrome associated with COVID-2019: the age ranged from 1 to 16 years. Fever lasting at least 3 days was observed in 100 % of the subjects. Evidence of multisystem disease occurred in all patients in particular: 8 children had tiny-dotted exanthema, 12 - pharyngitis; damage to the cardiovascular system in the form of cardiopathy was detected in 12 children, rhythm disorders in 15, dysmetabolic changes in the myocardium in 9; laboratory signs of coagulopathy in the form of an increased level of D-dimer were observed in 8 children, a decrease in thrombin time in 4; abdominal syndrome was found in 8 children. All patients had elevated levels of inflammatory markers. During the examinations, no convincing evidence of the presence of another disease that could cause these symptoms was found. All children had evidence of infection with the SARS-CoV-2 virus, namely, 9 had a history of COVID-19, 2 had a positive PCR test, 12 had IgG to COVID-19, and 5 had IgM to COVID-19. Conclusions. The article demonstrates the polymorphism of the clinical and laboratory manifestations of the multisystem pediatric inflammatory syndrome associated with COVID-2019; easy to use WHO criteria WHO criteria for diagnosing this syndrome; the need for every physician to be alert to this syndrome when in contact with a child who has fever for three or more days during the period of epidemic disorder due to coronavirus disease (COVID-19).